PENGOLAHAN DAN PEMASARAN PRODUK OLAHAN DARI BAHAN BAKU BUAH SALAK DI DUSUN GOWOK, POLENGAN MAGELANG - Yayat Hidayat (Universitas Muhammadiyah Yogyakarta, 2018)
Village Polengan Magelang it is village with a condition climate and soil the partile so many type ofplants and commodity thats grows and develops in its territory. This helped to boost the economy ofpeople. People income salak fruit is a mainstay of besides other plant as a supported. Bussinesdevelopment of salak fruit needs to perfect management of all a part of system. The problem of thissituation is how we found the solve or strategy to increase sales marketing corresponding by thispapers use descriptive analysis approach to make a map of problem was happened in DusunGowok. The result of analysis is showing the marketing is the fully ways system of bussines activity.